The Role and Practical Significance of the Art of Carving in Developing the Creative Skills of Young People (Journal of Universal Science Research, 2023)
This article examines the importance of carving as a means to enhance the creative skills of young individuals. It focuses on the specific context of carving a design on a circular mirror. The article highlights how carving provides a platform for young people to express their creativity and imagination. It emphasizes the development of manual dexterity and patience through the intricate process of carving. The article also explores how carving cultivates an appreciation for craftsmanship and cultural heritage, encouraging young individuals to explore diverse artistic traditions. Additionally, it discusses the practical significance of carving by fostering problem-solving abilities and critical thinking skills, which are transferable to various aspects of life. The article includes a table presenting statistics on the benefits of carving for young people, showcasing the positive outcomes reported by participants. Overall, this article provides a comprehensive overview of the role and practical significance of the art of carving in nurturing the creative skills of young individuals